CADM1 is a key receptor mediating human mast cell adhesion to human lung fibroblasts and airway smooth muscle cells. - Elena P Moiseeva (PLoS ONE, 2013)
Mast cells (MCs) play a central role in the development of many diseases including asthma and pulmonary fibrosis. Interactions of human lung mast cells (HLMCs) with human airway smooth muscle cells (HASMCs) are partially dependent on adhesion mediated by cell adhesion molecule-1 (CADM1), but the adhesion mechanism through which HLMCs interact with human lung fibroblasts (HLFs) is not known. CADM1 is expressed as several isoforms (SP4, SP1, SP6) in HLMCs, with SP4 dominant. These isoforms differentially regulate HLMC homotypic adhesion and survival.In this study we have investigated the role of CADM1 isoforms in the adhesion of HLMCs and HMC-1 cells to primary HASMCs and HLFs.CADM1 overexpression or downregulation was achieved using adenoviral delivery of CADM1 short hairpin RNAs or isoform-specific cDNAs respectively.Downregulation of CADM1 attenuated both HLMC and HMC-1 adhesion to both primary HASMCs and HLFs. Overexpression of either SP1 or SP4 isoforms did not alter MC adhesion to HASMCs, whereas overexpression of SP4, but not SP1, significantly increased both HMC-1 cell and HLMC adhesion to HLFs. The expression level of CADM1 SP4 strongly predicted the extent of MC adhesion; linear regression indicated that CADM1 accounts for up to 67% and 32% of adhesion to HLFs for HMC-1 cells and HLMCs, respectively. HLFs supported HLMC proliferation and survival through a CADM1-dependent mechanism. With respect to CADM1 counter-receptor expression, HLFs expressed both CADM1 and nectin-3, whereas HASMCs expressed only nectin-3.Collectively these data indicate that the CADM1 SP4 isoform is a key receptor mediating human MC adhesion to HASMCs and HLFs. The differential expression of CADM1 counter-receptors on HLFs compared to HASMCs may allow the specific targeting of either HLMC-HLF or HLMC-HASMC interactions in the lung parenchyma and airways.